Structural geometries and magnitude of shortening in the eastern Kura fold‐thrust belt, Azerbaijan: Implications for the development of the Greater Caucasus Mountains. Issue 3 (20th June 2013) - Forte, Adam M.; Cowgill, Eric; Murtuzayev, Ibrahim; Kangarli, Talat; Stoica, Marius
Abstract [1] The Greater Caucasus are the northernmost extent of the Arabia‐Eurasia collision and are thought to represent the main locus of shortening within the central portion of the collision zone between 40° and 48°E. Recent work suggests that in detail, since the Plio‐Pleistocene, much of the shortening in the eastern portion of the Caucasus system has been focused within the Kura fold‐thrust belt along the southeastern margin of the Greater Caucasus. Here we present new field mapping and stratigraphic investigations of the eastern termination of the Kura fold‐thrust belt in Azerbaijan to better constrain the structural geometries, magnitude of shortening, and initiation age for this portion of the fold‐thrust belt. Our work suggests that this area of the fold‐thrust belt exhibits significant along‐strike variations in structural style and evolution and can effectively be divided into two distinct domains at 48°E. The western domain is characterized by a subcritical median surface slope and isolated folds and thrusts propagating out of sequence, whereas the eastern domain is dominated by a single duplex structure and a history of in‐sequence development in a critically tapered wedge. We hypothesize that these variations result from changes in relative rates of syn‐tectonic sedimentation, erosion, and convergence velocity along strike. We find that within the western domain, the fold‐thrust belt has accommodated 12 km of total shortening. An unconformity within the western domain brackets the initiation age of this portion of the fold‐thrust belt to between 1.8 and 0.88 Ma yielding permissible average shortening rates of between 6.7 and 13.6 mm/yr. Comparison of these average shortening rates to the geodetically measured shortening rate of 8 mm/yr indicates that since initiation, the fold‐thrust belt has accommodated 83–100% of convergence between the Greater and Lesser Caucasus at this longitude.